UNIVERSITY STUDENTS’ PERCEPTIONS ON TIKTOK AS A DIGITAL LEARNING PLATFORM FOR PRONUNCIATION LEARNING - Hanif Wira Hestiningrum; Fajar Susanto (LPPM Universitas PGRI Jombang, 2025)
This study explores university students’ perceptions on TikTok as a digital learning platform for English pronunciation, considering the increasing role of social media in language education. The research aimed to identify how students perceive the benefits and challenges of using TikTok to enhance pronunciation learning. A qualitative case study design was applied, and the data were obtained through semi-structured interviews with five undergraduate students from the English Language Education Department of a private university in Surabaya. The study revealed three key findings: TikTok is perceived as a flexible and engaging supplementary tool that supports autonomous and enjoyable learning; its visual and repetitive features effectively facilitate observation and imitation of accurate pronunciation; and students maintain critical awareness of content quality, frequently validating information through reliable sources. The study concludes that TikTok provides significant potential as an informal platform for pronunciation development, while also emphasizing the necessity of digital literacy to optimize its educational use.